A comprehensive review on NUI, multi-sensory interfaces and UX design for applications and devices for visually impaired users - Arora, Lauryn; Choudhary, Akansh; Bhatt, Margi; Kaliappan, Jayakumar; Srinivasan, Kathiravan (Frontiers in Public Health, 2024)
In today's world, there has been a significant increase in the use of devices, gadgets, and mobile 16 applications in our daily activities. Although this has had a significant impact on the lives of the 17 general public, people who are Partially Visually Impaired (PVI), which includes a much broader 18 range of vision loss that includes mild to severe impairments, and Completely Visually Impaired 19 (CVI), who have no light perception, still face significant obstacles when trying to access and use 20 these technologies. This review article aims to provide an overview of the NUI, Multi-sensory 21 Interfaces and UX Design (NMUD) of apps and devices specifically tailored CVI and PVI 22 individuals. The article begins by emphasizing the importance of accessible technology for the 23 visually impaired and the need for a human-centered design approach. It presents a taxonomy of 24 essential design components that were considered during the development of applications and 25 gadgets for individuals with visual impairments. Furthermore, the article sheds light on the existing 26 challenges that need to be addressed to improve the design of apps and devices for CVI and PVI 27 individuals. These challenges include usability, affordability, and accessibility issues. Some common 28 problems include battery life, lack of user control, system latency, and limited functionality. Lastly, 29 the article discusses future research directions for the design of accessible apps and devices for 30 visually impaired individuals. It emphasizes the need for more user-centered design approaches, 31 adherence to guidelines such as the Web Content Accessibility Guidelines, the application of e-32 accessibility principles, the development of more accessible and affordable technologies, and the 33 integration of these technologies into the wider assistive technology ecosystem.